Alone on the Snow, Alone on the Beach: “A Global Sense of Place” in Atanarjuat and Fountain - Horton, Jessica L. (eScholarship, University of California, 2012)
Recently, scholars and artists have queried the relationship between indigenous places—defined by their unique histories and meanings—and abstract spatial metaphors attending a current period of globalization. In this essay, Horton revisits two well-known works of digital video by Native North American artists to consider how they resolve an apparent tension between the indigenous lands they depict and the global networks in which they circulate: the internationally popular feature-length film Atanarjuat, the Fast Runner (2001), directed by Inuit artist Zacharias Kunuk, and the short video work Fountain (2005), created by Anishinaabe artist Rebecca Belmore for the Canadian Pavilion at the Venice Biennale. Both works feature human bodies interacting with tactile substances like ice and water, spiritual forces at work in the environment, and landscapes that fade in and out of abstraction. Their creative approaches to sound, montage, and projection techniques set in motion dialectics of displacement and emplacement. Atanarjuat and Fountain contribute to an expansive notion of indigenous places, one that values the historical and cultural specificity of locales as the starting point for unraveling the complexities of their relationships to distant people and places.